A Cognitive Construal of the Concessive Conditional Construction “ Because Doesn’t ”: A Corpus-Based Study - Songsong Zhang; Jinyang Hu; Xueyu Sun (SAGE Open)
This study takes the English concessive conditional construction “ Just Because X Doesn’t Mean Y ” (JBX-DMY) as its object, extracts instances from the Corpus of Contemporary American English (COCA), applies Simple Collostructional Analysis to the representative collexemes, and investigates the experiential and conceptual characteristics of this construction from the perspective of cognitive construal in order to explain the source and mechanism of polysemy. Dividing JBX-DMY into two parts, this study analyzes ways of construal, vantage points and viewing arrangement under the dimension of cognitive construal.